Neurological and Neuropsychological Changes Associated with SARS-CoV-2 Infection: New Observations, New Mechanisms. (December 2022) - Haidar, Muhammad Ali; Jourdi, Hussam; Haj Hassan, Zeinab; Ashekyan, Ohanes; Fardoun, Manal; Wehbe, Zena; Maaliki, Dina; Wehbe, Maya; Mondello, Stefania; Abdelhady, Samar; Shahjouei, Shima; Bizri, Maya; et al.
SARS-CoV-2 infects cells through angiotensin-converting enzyme 2 (ACE2), a ubiquitous receptor that interacts with the virus' surface S glycoprotein. Recent reports show that the virus affects the central nervous system (CNS) with symptoms and complications that include dizziness, altered consciousness, encephalitis, and even stroke. These can immerge as indirect immune effects due to increased cytokine production or via direct viral entry into brain tissue. The latter is possible through neuronal access via the olfactory bulb, hematogenous access through immune cells or directly across the blood-brain barrier (BBB), and through the brain's circumventricular organs characterized by their extensive and highly permeable capillaries. Last, the COVID-19 pandemic increases stress, depression, and anxiety within infected individuals, those in isolation, and high-risk populations like children, the elderly, and health workers. This review surveys the recent updates of CNS manifestations post SARS-CoV-2 infection along with possible mechanisms that lead to them.